EFEKTIFITAS INSTAGRAM SEBAGAI MEDIA PERSUASI FILANTROPI ISLAM BAGI MAHASISWA - herlina yustati (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2019)
Through this paper the author will measure the effectiveness of Instagram as a media for persuasion of Islamic philanthropy for students. Because Instagram is a social media that is in great demand by the younger generation. This research is a quantitative study with a questionnaire as a research instrument, population for tihis research was students of the zakat waqf management study program of IAIN Bengkulu, sample was a saturated sample,   consist of 76 students. Measuring the level of effectiveness using the AIDA method (Attention, Interest, Desire and Action). The results showed that the effectiveness of Instagram was in the good category as a persuasion media for Islamic philanthropy for students.